(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2024)
This paper seeks to explore sex and fear in the therapy room through a Sartrean lens. It aims to engage with his ideas on love, desire and sexuality as a response to Heidegger’s ontology, and to ask whether we can find a link between fear and our relationship to freedom.